Quantitative Charge-Tags for Sterol and Oxysterol Analysis. (6th January 2020) - Crick, Peter J; William Bentley, T; Abdel-Khalik, Jonas; Matthews, Ian; Clayton, Peter T; Morris, Andrew A; Bigger, Brian W; Zerbinati, Chiara; Tritapepe, Luigi; Iuliano, Luigi; Wang, Yuqin; Griffiths, William J
Abstract: BACKGROUND: Global sterol analysis is challenging owing to the extreme diversity of sterol natural products, the tendency of cholesterol to dominate in abundance over all other sterols, and the structural lack of a strong chromophore or readily ionized functional group. We developed a method to overcome these challenges by using different isotope-labeled versions of the Girard P reagent (GP) as quantitative charge-tags for the LC-MS analysis of sterols including oxysterols. METHODS: Sterols/oxysterols in plasma were extracted in ethanol containing deuterated internal standards, separated by C18 solid-phase extraction, and derivatized with GP, with or without prior oxidation of 3β-hydroxy to 3-oxo groups. RESULTS: By use of different isotope-labeled GPs, it was possible to analyze in a single LC-MS analysis both sterols/oxysterols that naturally possess a 3-oxo group and those with a 3β-hydroxy group. Intra- and interassay CVs were <15%, and recoveries for representative oxysterols and cholestenoic acids were 85%–108%. By adopting a multiplex approach to isotope labeling, we analyzed up to 4 different samples in a single run. Using plasma samples, we could demonstrate the diagnosis of inborn errors of metabolism and also the export of oxysterols from brain via the jugular vein. CONCLUSIONS: This method allows the profiling of the widest range of sterols/oxysterols in a single analytical run and can be used to identify inborn errors of cholesterol synthesis and metabolism.